Knowledge and Attitude Risky Transvestite with the Scene Sexually Transmitted Infection (STI) on Transvestite in Sidoarjo - Resti Suwandani (Universitas Airlangga, 2015)
The World Health Organization in 2005 stated that 457 million people worldwide had sexually transmitted infections. Transvestites are one of the high-risk groups for contracting Sexual Transmitted Disease (STD/STI) and Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV/AIDS). This study aims to look at transvestite/ transsexuals risky sexual behavior which includes knowledge and attitudes related to the incidence STD of transsexuals in Sidoarjo. This study uses an analytic research design in which the type of research is case-control. Respondents in the study were transvestites who were within the reach of the National AIDS Commission, Sidoarjo with 54 people divided into two groups, 18 case groups, and 36 control groups. The age of respondents from both groups is the same, that is > 40 years, the education level of the highest case group is junior high school and the control group is the senior high school, the marital status of the two groups is the same, that is unmarried, the most work in the case group is sex workers and in the control group salon workers, the long be the transvestites in the case group is for 1–12 years and in the control group 13–24 years. There is a relationship between knowledge and the incidence of STD in transvestites (p=0.007) p <α. There is a relationship between attitude and the incidence of STD in transvestites (p = 0.001) p<α.